A New Pyrrolidone Alkaloid and Other Constituents from Rourea oligophlebia Stems - Thuc Ngoc Dinh; Mai Vu Thi Ha; Luong Ngo Xuan; Huan Trinh Thi; Huong Nguyen Thi; Mai Nguyen Thi Ngoc; Giap Tran Huu; Oanh Vu Thi Kim; Thanh Le Nguyen (Journal of Chemistry)
Phytochemical study of Rourea oligophlebia stems led to the isolation of a new 2-pyrrolidone alkaloid (R,S)-N-(5-hydroxyl-pyrrolidin-2-one-1-yl)acetamide (1), together with 14 known compounds including friedelin (2), friedanol (3), taraxerol (4), vanillin (5), coniferyl aldehyde (6), apigenin (7), 7α-hydroxy-3β-sitosterol (8), coniferyl alcohol (9), scopoletin (10), emodin (11), protocatechuic acid (12), catechin (13), procyanidin A1 (14), and (E)-2,3,5,4’-tetrahydroxystilbene-2-β-D-glucoside (15). Several isolated compounds were evaluated for cytotoxicity and antimicrobial activity. Compound 11 exhibited good antimicrobial activity on Gram (+) strains and moderate cytotoxicity against KB, Hep-G2, and LU cancer cell lines. Compounds 6 and 8–10 showed selective activity on HepG-2 and MCF-7 over KB and LU cancer cell lines, while compound 7 exhibited similar effects on KB, HepG-2, and MCF-7 cell lines with IC50 values of 36.46 ± 0.81, 32.00 ± 0.58, and 32.03 ± 0.61 µg/mL, respectively.